English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

complete the square for this equation

2x^2 - 4x - 7 = 0

2006-12-05 05:50:46 · 2 answers · asked by Twista-Adzy 2 in Science & Mathematics Mathematics

2 answers

2x² - 4x - 7 =0

2x² - 4x - 7 + 7 = 0 + 7

2x² - 4x = 7

2x² / 2 - 4x / 2 = 7 / 2

x² - 2x = 7 /2

x² - 2x + 1 - 7 / 2 + 1

(x - 1)(x - 1) = 7 /2 + 2 / 2

(x - 1)² = 9/2

(x - 1)² = √4.5

x - 1 = ± √4.5

x - 1 + 1 = 1 ± √4.5

x = 1 ± √4.5

- - - - -s-

2006-12-05 07:06:40 · answer #1 · answered by SAMUEL D 7 · 0 0

2x^2-4x=7
x^2-2x=7/2
x^2-2x+1=7/2+1
(x-1)^2=9/2

2006-12-05 13:55:03 · answer #2 · answered by raj 7 · 0 0

fedest.com, questions and answers